Shelf-life testing of dehydrated lacatan banana (Musa sapientum var lacatan) under refrigerated temperature - Ferrer, Aira Czarina C.; Villarino, Blanca J. (c2011.)
ABSTRACT This study aimed to determine the shelf life of cabinet dried Lacatan bananas under refrigerated storage. Specifically, it involved the assessment of the effects of various antibrowning agents on dehydrated Lacatan banana. Likewise, changes on the treated dehydrated Lacatan banana under refrigerated storage were evaluated. Sodium metabisulfite (0.25%), citric acid (1%) and pineapple juice were considered as antibrowning treatments. Physicochemical analyses involved the assessment of color (L*, a*, b*), water activity (aw) and moisture content (MC) while sensory evaluation included over-all acceptability (OA), color, odor, flavor and chewiness. Shelf life of dried banana under chilled storage was determined through sensory evaluation (acceptance and intensity), microbiological analysis (Total Plate Count and Yeast and Mold Count) and physicochemical tests (aw and MC). Significant (p<0.05) dependence of color (L*, a*, b*), aw and MC (dry and wet basis) on the type of pretreatment used on dehydrated Lacatan were observed. Over-all acceptability and chewiness also revealed the same result while color, odor and flavor were not dependent on the type of treatment used. Pineapple juice was found to be the most appropriate antibrowning agent for Lacatan bananas. Storage of the treated Lacatan banana shows that Aw increased while MC almost neither increased nor decreased in time. Over-all acceptability, color acceptability and ratings also increased through time. On the other hand, odor, flavor and chewiness acceptability and ratings decreased during storage. Microbiological examination showed that shelf life was limited by the unacceptable total plate count on the 17th day of storage. The study presented that pineapple treated dehydrated Lacatan banana had a shelf life of 14 days.
ABSTRACT
Thesis(BSFT)--University of the Philippines Diliman
Keywords: Bananas